The Effect of Factors on Dividend Policy - Nuryaman (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to test the factors that can affect the amount of dividend distribution, a study of companies included in the LQ 45 group on the Indonesia Stock Excange. Sampling using a purposive sampling method, obtained a total sample of 24 companies for the observation period of 2013-2017, so as many as 120 data were obtained. The test results show that profitability (ROA, ROE) and leverage have been proven to influence dividend distribution policy. Profitability and leverage are important factors in dividend distribution decisions. Furthermore, this study failed to prove the company’s liquidity as an important factor in dividend distribution. Testing data shows that liquidity do not significantly influence dividend distribution.